Geopolymer vs ordinary portland cement: review of the 3-d printing of concrete - Hamed Rahimpour; Vahed Ghiasi; Ahmad Fahmi; Yaser Marabi (Applied Engineering and Technology, 2023)
Due to the need of the construction industry to implement structures with special and complex designs, mass customization with the lowest cost, especially reducing the labor cost as well as the amount of waste and materials used, the use of concrete 3D printing can be the appropriate solution to these requirements fulfill these options. As a result, a comprehensive and practical study of the major 3D printing methods and their development in the construction industry was carried out in this study. In addition, the use of OPC-based materials and geopolymer-based materials was reviewed and compared due to the development of the materials industry and the advantages and disadvantages of using different types of cementitious materials in the 3D printing of concrete.